A Ligation-PCR Approach for Generating Gene Replacement Constructs in Magnaporthe grisea - Xinhua Zhao; Chaoyang Xue; Yangseon Kim; Jin-Rong Xu (Fungal Genetics Reports, 2004)
The conventional approach for generating gene replacement constructs involves several sequence-specific cloning steps and is time-consuming. A ligation-PCR approach was developed to efficiently generate gene replacement constructs. Two vectors useful for this ligation-PCR approach and another vector suitable for improving the efficiency of knockout mutant screens were constructed.